Portfolio Optimization Using The Capital Asset Pricing Model (CAPM) And Multi Index Model In LQ45 Companies - Bayu Arifin; Dudi Rudianto (Sean Institute, 2024)
This study aims to determine the results of portfolio optimization using the Capital Asset Pricing Model (CAPM) and Multi Index Model in LQ45 companies. The research utilizes monthly stock data that consistently appear in the LQ45 index on the Indonesia Stock Exchange from 2012 to 2022. Seventeen stocks were selected: ADRO, ASII, BBCA, BBNI, BBRI, BMRI, ICBP, INCO, INDF, INTP, KLBF, MNCN, PTBA, SMGR, TLKM, UNTR, and UNVR. The data was collected from January 2012 to December 2022. Using the CAPM model, no optimal portfolio was formed. However, using the Multi Index Model, an optimal portfolio was formed consisting of four stocks: INDF, INTP, MNCN, and TLKM, generating a return of 0.28% and a risk of 1.29%. This study concludes that the Multi Index Model is capable of demonstrating optimal portfolio results.